MiR-29b defines the pro-/anti-proliferative effects of S100A7 in breast cancer. Issue 1 (December 2015) - Zhao, Helong; Wilkie, Tasha; Deol, Yadwinder; Sneh, Amita; Ganju, Akaansha; Basree, Mustafa; Nasser, Mohd; Ganju, Ramesh
Abstract Introduction S100A7 (Psoriasin) is an inflammatory protein known to be upregulated in breast cancer. However, the role of S100A7 in breast cancer has been elusive, since both pro- and anti-proliferative roles have been reported in different types of breast cancer cells and animal models. To date, the mechanism by which S100A7 differentially regulates breast cancer cell proliferation is still not clear. Methods We used Gene Functional Enrichment Analysis to search for the determining factor of S100A7 differential regulation. We confirmed the factor and elaborated its regulating mechanism usingin vitro cell culture. We further verified the findings using xenografts of human breast cancer cells in nude mice. Results In the present study, we show that S100A7 significantly upregulates the expression of miR-29b in Estrogen Receptor (ER)-positive breast cancer cells (represented by MCF7), and significantly downregulates miR-29b in ER-negative cells (represented by MDA-MB-231). The differential regulation of miR-29b by S100A7 in ER-positive and ER-negative breast cancer is supported by the gene expression analysis of TCGA invasive breast cancer dataset. miR-29b transcription is inhibited by NF-κB, and NF-κB activation is differentially regulated by S100A7 in ER-positive and ER-negative breast cancer cells. This further leads to differential regulation of PI3K p85α and CDC42 expression, p53 activation and p53-associated anti-proliferative pathways. Reversing the S100A7-caused changes of miR-29b expression by transfecting exogenous miR-29b or miR-29b-Decoy can inhibit the effects of S100A7 onin vitro cell proliferation and tumor growth in nude mice. Conclusions The distinct modulations of the NF-κB – miR-29b – p53 pathway make S100A7 an oncogene in ER-negative and a cancer-suppressing gene in ER-positive breast cancer cells, with miR-29b being the determining regulatory factor.